Spinning for the gods? Preliminary observations on prehistoric textile production at Hierakonpolis, Egypt - Drewsen, Anne (Archaeological Textiles Review, 2019)
Around 3500 BC, an adult elephant was sacrificed and buried in the elite cemetery of Hierakonpolis in the very south of Egypt. The elephant was given a burial similar to humans including a linen shroud. This shroud is just one of an impressive number of textiles found at the site illustrating a range of uses. The textiles of the late prehistory in Egypt, the predynastic period, have not yet been thoroughly researched, and the linen of the elephant’s shroud therefore presents a unique opportunity to consider the time used to produce it and the expertise of the spinners and weavers. The information from textile tools found at Hierakonpolis can now also be added to this story. The results of research into the elephant’s shroud and the textile tools question our perception of prehistoric society in Egypt just before state formation, especially in relation to the organisation of textile production.